KONSEP MULTIKULTURALISME DAN PLURALISME DALAM PENDIDIKAN AGAMA (Upaya Menguniversalkan Pendidikan Agama dalam Ranah Keindonesiaan) - Muhandis Azzuhri (IAIN Pekalongan, 2012)
Multiculturalism and pluralism are characters that could not beÂ denied in the education system of Indonesia, especially in religious education.Through that concept, a sense of unity within the realm of ukhuwah basyariyahin promoting and improving the quality of education will be established; therefore the educational system which makes religion as moral values and not as formal institutional is formed.